Alpha-Lipoic Acid Improves Acetic Acid-Induced Gastric Ulcer Healing in Rats - YEGEN, BERRAK; ERZİK, CAN; ERCAN, FERİHA; YÜKSEL, MERAL (SPRINGER/PLENUM PUBLISHERS, 2009)
To evaluate the role of ALA treatment on the healing of acetic acid-induced gastric ulcer, rats were given ALA (35 mg/kg/day) or saline for 3 days before the induction of ulcer and the treatment was continued twice daily for 2 days (early) or 10 days (late) until they were decapitated. Gastric ulcer index, microscopic score, elevated DNA fragmentation and chemiluminescence levels of the saline-treated ulcer groups were all reduced by ALA treatment. Likewise, ALA treatment inhibited chemiluminescence levels in both early and late ulcer groups. Marked reduction in glutathione levels of the saline-treated early ulcer group was reversed by ALA treatment, while ALA treatment was effective in depressing gastric myeloperoxidase activity in the late ulcer group. In conclusion, ALA treatment shows protective role in the healing of acetic acid-induced gastric injury in rats via the suppression of neutrophil accumulation, preservation of endogenous glutathione, inhibition of reactive oxidant generation and apoptosis.
Keywords: alpha-lipoic acid; ulcer healing; acetic acid; oxidant damage; apoptosis; NF-KAPPA-B; OXIDATIVE STRESS; LIPID-PEROXIDATION; GENE-EXPRESSION; L-CARNITINE; ANTIOXIDANT; APOPTOSIS; CELLS; DAMAGE; INFLAMMATION